Modern economic and geographical characteristics and prospects of development of environmental protection infrastructure in the Baikal region of Russia - Zabortseva, Tatiana (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2011)
In the administrative division of Russia, the Baikal region is traditionally considered as embracing three parts: the Irkutsk oblast’, the Republic of Buryatia, and Zabaikalsky Kray. Its area is three times larger than that of France (1.6 million km²), but its population size and density are typical of “the Siberian depth of the country” (4.6 million people, under 3 persons/km²). One of the most important global features of a part of this region – the Baikal Natural Territory – is to ensure the preservation of Lake Baikal as a World Heritage Site. A strategy of environmentally oriented land use determines an adequate level of development of ecological infrastructure and its most important sector – environmental protection infrastructure (EPI). The article presents an analysis of the current infrastructure for managing solid waste, and proposes a forecast scenario of its development with the use of the gravity model in the EPI sector involving recycling collection points.
Keywords: territorial organisation; environmental protection infrastructure; gravity model; Baikal region